Exogenous Cushing Syndrome pada Kasus Systemic Lupus Erythematosus - I Gusti Agung Ayu Indrayuni; Wira Gotera; Ida Bagus Aditya Nugraha (Universitas Pahlawan Tuanku Tambusai, 2026)
Cushing's syndrome (CS) is a group of signs and symptoms caused by chronic exposure to excess glucocorticoids. There are two types of Cushing's syndrome, endogenous and exogenous. Exogenous Cushing's syndrome, is a consequence of prolonged exposure to glucocorticoid drugs. Hypercortisolism is characterized by specific clinical features (moon face, facial plethora, striae rubrae, and supraclavicular and dorsal fat pads), as well as metabolic complications such as visceral obesity, hypertension, diabetes, dyslipidemia, osteoporosis, and detrimental effects on the brain, including hippocampal damage and memory impairment. Exogenous Cushing's syndrome is characterized by low serum cortisol levels in the morning. Discontinuation of exogenous glucocorticoids is the main pillar that must be carried out in exogenous Cushing's syndrome